Early Use of Remdesivir in Patients Hospitalized With COVID-19 Improves Clinical Outcomes: A Retrospective Observational Study. Issue 5 (September 2021) - Paranjape, Neha; Husain, Mir; Priestley, Jennifer; Koonjah, Yashila; Watts, Christopher; Havlik, Joseph
Abstract : Background: Remdesivir treatment, like most antiviral drugs, is likely to be most effective when used early in the course of coronavirus disease 2019 (COVID-19). Optimal timing of remdesivir for the treatment of COVID-19 remains unclear. Objectives: The aim of this study was to determine whether early treatment with remdesivir improves clinical outcomes: length of stay, need for mechanical ventilation, and death. Methods: We conducted a retrospective observational study of patients hospitalized with COVID-19 who received remdesivir therapy within 10 days of symptom onset at a large health system in Georgia, United States. Results: We identified a total of 475 patients. Initiation of therapy 3 days or less from first positive SARS-CoV-2 improved length of stay (15.7 days) compared with those started on therapy more than 3 days after a positive test (19.3 days) ( P = 0.03). In the ⩽3 day group, further reduction in length of stay was seen in those with lower oxygen requirement at baseline ( P < 0.0001). Length of stay was lower in the ⩽3 day group both with and without the use of corticosteroids ( P = 0.0003). The odds of requiring mechanical ventilation were higher for the >3 day group compared with the ⩽3 day group (odds ratio, 1.5; 95% confidence interval, 0.8–2.7), and the odds of death were higher for the >3 day group versus the ⩽3 day group (odds ratio, 1.74; 95% confidence interval, 0.9–3.2). Conclusions: Our data show that early treatment with remdesivir in patients hospitalized with COVID-19 shortened length of stay.